Técnica processual e tutela coletiva de interesses ambientais trabalhistas : os provimentos mandamentais como instrumentos de proteção da saúde do cidadão-trabalhador - Cesário, João Humberto (2011)
The current dissertation is focused on the use of the procedural technic for the collective protection of environmental labor concerns. It considers, initialy, some reflections on the historical factors that led to the creation of the labor law, in order to clarify the premises that have been the basis of its classic conformance. It denounces, afterwards, what it names as the the original lure of labour law, understood as the juridical option of postponing the establishment of labour law obligations, concerning to the adequacy of the working environment, intending to prioritize the payment of economic benefits, unhelpful to preserv the health of workers. Then, it suggests a model of approach between labour law and environmental law, which allows the first, based on the principles of the second, to suitably fulfill its defensive promise. Subsequently, it studies the possibilities of using the procedural law to inhibit and / or to overcome the labour environment crisis, mainly from the utililization of the class action. It shows, eventually, from doctrinal and practical perspectives, the different ways to use the commandment decisions to reduce the risks of work, focusing attention on inhibitory, ilicit removal and in the specific way idemnifying proceedings.